The Master of Library Science graduates of the University of the Philippines Institute of Library Science a follow up study - Monroy, Corazon B. (1982)
This study is a survey of the graduates of the Master of Library Science degree of the Institute of Library Science, University of the Philippines, for the years 1966-1980. Sixty-one out of 110, the total number of graduates, responded to a questionnaire intended to gather data for the study the main purposes of which are to know the types of jobs the UPMLS graduates are engaged in and to determine the factors related to their job satisfaction and dissatisfaction. The survey also aims to obtain feedback about the relevance of the course to the graduates' jobs and at the same time to determine the phase/phases of the course which should be improved such that it may render more effective service to the students. In addition it aims to ascertain the number of graduates not engaged in library work and their reasons for leaving the field.